The Phenomenon of Marriage Cancellation Due to the High Panai Money in the Makassar Bugis Marriage Tradition and Its Potential for Suicide Behavior - Nurwahyuni Nurwahyuni; Ainayah Alfatihah; Dina Mutiatunnisa; Lishariani La Alewu; Misnawaty Usman (HUMAN: South Asian Journal of Social Studies, 2021)
This study was conducted to describe the phenomenon of marriage annulment due to high panai money in the Bugis Makassar marriage tradition, the factors that lead to high panai money, and its potential for suicidal behavior. The type of research used is qualitative research with a phenomenological approach. The data in this study are primary data covering people who have experienced marriage annulment due to the high amount of panai money. The source of the data for this research is interview with the interviewees. Data collection techniques were carried out through interviewing sources. The research instrument is the researcher himself. Data analysis techniques in this study are verbatim, coding, data presentation, and inference. The results of the research obtained are a description of the phenomenon of marriage annulment due to high pennies, marriage cancellations can occur if the nominal panai set by the woman is too high so that it cannot be fulfilled by the men. The man's family will ultimately choose to cancel the wedding plan rather than force the woman's will. The factors that lead to high paychecks are the social strata of the family, education and work, as well as the physical condition of the women. The potential for suicidal behavior by people who have annulled marriages, while the results found indicate that the phenomenon of marriage annulment due to high wages has the potential to occur suicidal behavior in couples who experience annulment of marriageKeywords: Marriage Tradition, Panai Money, Marriage Annulment, Suicidal Behavior.